(untitled) (Journal of Organizational Psychology, 2016)
Using an inductive qualitative approach, this study examined perceptions of helicopter parents in the workplace. An analysis of 596 comments posted to online discussion boards revealed four major themes (1) attributions (i.e., someone is to blame including the helicopter parents, the adult children, and/or the company), (2) impression formation (e.g., adult children of helicopter parents are incompetent, unreliable, unable to work independently), (3) boundaries/separation (parents are over-stepping important boundary), and (4) the appropriateness of parental involvement in the workplace. Based on the qualitative analysis, a theoretical model and a set of propositions are discussed